The Analysis Sistem Informasi Manajemen Daerah (SIMDA) At Badan Pengelolaan Keuangan Dan Aset Daerah (BPKAD) Kota Semarang Using Technology Acceptance Model (TAM) - Rahmawati Ulfah; Dwi Rachmawati; Nur Fitri Dewi; Agnemas Yusoep Islami; Zakia Maulida Antono (International Publisher, 2023)
The purpose of this study is to analyze the Regional Management Information System (SIMDA) in BPKAD Semarang City, assessed based on the level of ease of use, usability, attitude towards use, and actual usage using TAM (Technology Acceptance Model). Data were obtained through interviews and questionnaires. The population consists of all employees who are active users of SIMDA. The analytical model employed in this study is the Structural Equation Model (SEM), while the software used is SmartPLS 2.0 M3. The results of hypothesis testing and discussions indicate that perceived ease of use has a significant positive influence on perceived usefulness. Perceived usefulness, in turn, has a significant positive influence on attitude towards use. Perceived ease of use also has a significant positive influence on attitude towards use. Finally, attitude towards use has a significant positive influence on actual system usage.